Surgical exploration without resection in pancreatic and periampullary tumors: Report from a national database. (September 2021) - Sahlström, Emil; Nilsson, Johan; Tingstedt, Bobby; Bergenfeldt, Magnus; Andersson, Roland; Andersson, Bodil
Background and objective: Pancreatic and periampullary cancers are sometimes found to have a too advanced disease during surgery to allow resection. The aim was to describe characteristics, treatment, outcome, and time trends for patients that were planned for pancreatic surgery but found unresectable during surgery. Methods: Data from the Swedish National Pancreatic and Periampullary Cancer Registry were used. All patients registered between January 2010 and August 2018 were included. The patient cohort was divided in two halves based on year of diagnosis. Results: In total, 12, 377 patients were included in the registry and finally 4568 patients were scheduled for surgery. During surgical exploration, 3879 (84.9%) patients underwent pancreatic resection, 658 (14.4%) patients were found unresectable, and 31 (0.7%) had no pancreatic resection due to other reasons (e.g. benign lesion, comorbidity). More patients underwent surgical exploration and resection during the second time period, but exploration without resection was unchanged (15.7% vs 13.7%; p = 0.062). Survival rates were lower among the unresectable patients with pancreatic and periampullary tumors compared to the resectable patients, including 30-day mortality (n = 17 (3.5%) vs n = 39 (1.6%), p = 0.004) and 90-day mortality (n = 72 (15.0%) vs n = 70 (2.8%), p < 0.001). Palliative surgery became less common during the second half of the time period (p < 0.001). Conclusions: Unresectability is associated with an unfavorable prognosis. The frequency did not decrease during the study period, but palliative surgical procedures became less common.